Comparative Analysis of the Use of Coarse Aggregate from Merak and Coarse Aggregate from Batu Gadur on the Compressive Strength of Normal Quality Concrete - Lilis Indriani; Budi Tjahjono (CV. Creative Tugu Pena, 2026)
Concrete is a widely used construction material whose mechanical performance is strongly influenced by the properties of its constituent materials, particularly coarse aggregates. This study investigates the comparative effect of coarse aggregates sourced from Merak and Batu Gadur on the compressive strength of normal strength concrete. An experimental laboratory-based method was employed using concrete cube specimens measuring 150 mm × 150 mm × 150 mm. Three mixture variations were prepared: concrete with 100% Merak coarse aggregate, concrete with 50% Merak and 50% Batu Gadur coarse aggregate, and concrete with 100% Batu Gadur coarse aggregate. All specimens were cured and tested for compressive strength at 7 and 28 days. The results indicate that concrete containing 100% Merak aggregate exhibited stable and continuous strength development, while the 50% substitution mixture maintained relatively consistent compressive strength across curing ages. In contrast, concrete produced with 100% Batu Gadur aggregate achieved high early-age strength but showed a significant reduction at 28 days. These findings demonstrate that Batu Gadur aggregate can be utilized as a partial replacement for Merak aggregate at proportions not exceeding 50% without compromising concrete performance. This study supports the use of local aggregates to enhance sustainability in construction practices.